Physics and technology of magnetron sputtering discharges - Gudmundsson, J T (Plasma sources science & technology, 2020)
Magnetron sputtering deposition has become the most widely used technique for deposition of both metallic and compound thin films and is utilized in numerous industrial applications. There has been a continuous development of the magnetron sputtering technology to improve target utilization, increase ionization of the sputtered species, increase deposition rates, and to minimize electrical instabilities such as arcs, as well as to reduce operating cost. The development from the direct current (dc) diode sputter tool to the magnetron sputtering discharge is discussed as well as the various magnetron sputtering discharge configurations. The magnetron sputtering discharge is either operated as a dc or radio frequency discharge, or it is driven by some other periodic waveforms depending on the application. This includes reactive magnetron sputtering which exhibits hysteresis and is often operated with an asymmetric bipolar mid-frequency pulsed waveform. Due to target poisoning the reactive sputter process is inherently unstable and exhibits a strongly non-linear response to variations in operating parameters. Ionized physical vapor deposition was initially achieved by adding a secondary discharge between the cathode target and the substrate and later by applying high power pulses to the cathode target. An overview is given of the operating parameters, the discharge properties and the plasma parameters including particle densities, discharge current composition, electron and ion energy distributions, deposition rate, and ionized flux fraction. The discharge maintenance is discussed including the electron heating processes, the creation and role of secondary electrons and Ohmic heating, and the sputter processes. Furthermore, the role and appearance of instabilities in the discharge operation is discussed.